Decoupling between chain extension and entanglement via branched structures for ultralow-power biaxially stretched polypropylene capacitor films - Qi Wu; Can Zhao; Enhui Liu; Xuan Wang; Jing Zhou; Rui Han; Min Nie (Chemical Engineering Journal, 2026)

Dielectric gradient C@SiC@SiO2 microspheres for broadband room-temperature microwave absorption - Zhixiao Wang; Qun Li; Tao Yang; Qiuye Liu; Kang Wang; Enhui Wang; Yanglong Hou; Xinmei Hou (Chemical Engineering Journal, 2026)

35-Micrometer-thick zincophilic polyimide separator for energy-dense aqueous zinc-ion batteries - Hanling Guo; Enhui Zhang; Shixiao Wang; Zhen Wu; Fengxian Gao; Xiang Lin; Min Gong; Liang Zhang; Dongrui Wang (Chemical Engineering Journal, 2026)

Methoxycarbonylation of ethylene/ethane mixture to methyl propionate over Pd-phosphine system with H-Beta zeolite and sulfonic acid as acid promoters - Shaoxia Guo; Mengting Li; Liang Gao; Yongrui Wang; Cheng Gu; Longxiao Yang; Yuping Huang; Enhui Xing; Yibin Luo; Xinbin Ma; Xingtian Shu (Chemical Engineering Journal, 2026)

The Coupling Coordination and Spatio-temporal Evolution of Water-energy-food in the Yellow River Basin - Ken Sun; Xinyu Chen; Jiacheng Liu; Enhui Shi; Yuanbiao Wang; Yiting Zhou; Xiaotong Xing; Jiabin Chen (Water, Air, & Soil Pollution, 2026)

Coupling coordination and spatiotemporal evolution of water and energy welfare performance in 35 cities of the Yellow River Basin, 2010–2019 - Ken Sun; Xiaotong Xing; Jiacheng Liu; Enhui Shi; Yuanbiao Wang; Yiting Zhou; Xinyu Chen (Environment, Development and Sustainability, 2026)

Unveiling the occurrence and ecological risks of phthalate esters in the municipal wastewater treatment plant by a specific fragment-based GC-EI&PCI-HRMS method - Yinuo Xiao; Kun Wang; Jinsong Liu; Jing Wang; Zhengzheng Liu; Qinqin Sun; Chaoming Zhang; Enhui Wu; Jiahui Yang; Baoliang Chen (Water Research, 2026)

Rapid detection of porcine circovirus type2 using a combination of RAA isothermal amplification and Cas12a nucleic detection technology - Lejia Fan; Xueming Liu; Jiaqing Hu; Jinjin Chi; Xiaoyu Fei; Chao Qi; Enhui Wang; Feng Su (Research in Veterinary Science, 2026)

A novel forest fire scenario deduction method based on belief rule base - Rui Zhao; Ning Wang; Wenguang Yan; Enhui Zhao (Natural Hazards, 2026)

Effect of explicit intermediate layer on the solution accuracy of the thermal stress for printed circuit heat exchangers with the homogenization method - Xiaoxu Zhang; Zirui Xu; Enhui Li; Yin Tan; Jiyuan Bi; Dan Zheng; Sheng Wang; Ting Ma (Annals of Nuclear Energy, 2026)

GEFmeso restricts JAK/STAT signaling to regulate border cell migration in Drosophila melanogaster - Liying Shi; Yuanyuan Song; Jiahang Li; Xiping Yu; Yanchao Wang; Ling Jiang; Enhui Shao; Ping Wan (Insect Biochemistry and Molecular Biology, 2026)

A novel river pattern classification rule based on geometric parameters of channel planform - Zhou Yang; Enhui Jiang; Yanhui Liu; Yuanjian Wang; Wanjie Zhao; Gang Liu (CATENA, 2026)

Photoreactive bromide ions as overlooked regulators of nanoplastic surface chemistry and aggregation in sunlit seawater - Xinjie Wang; Enhui Jiang; Yining Wang; Jian Zhao; Shuang Xu; Xinghui Xia; Yang Li (Water Research, 2026)

Sesquiterpenoids with anti-neuroinflammatory effects in vitro from Laggera alata - Xingxi Li; Wenhao Qiao; Qian Yang; Mingzhu Hu; Enhui Wang; Rongping Zhang; Xinglong Chen (Phytochemistry Letters, 2026)

Enhanced photodynamic therapy induces dual nuclear/mitochondrial DNA damage and cGAS/STING-driven innate immunity for improved colorectal cancer immunotherapy - Dexiang Zhu; Weijun Huang; Yutong Wang; Yuxiao Yang; Fanghua Su; Chuyue Lu; Zhenyu Lin; Enhui Zhou; Zhian Chen; Ruiyuan Liu; Qianbing Zhang (Chemical Engineering Journal, 2026)

Adipocytes as core drivers of skin aging and novel targets for regeneration - Enhui Wang; Zijun Xu; Yuting Wang; Junbo Wang; Yanfei Jiang; Chunyue Zhao (Biogerontology, 2026)

Optimal selection and fusion framework of multi-source soil moisture data based on climate zoning and cross attention - Enhui Wang; Xinghao Li; Junran Yang; Junming Shao; Guoqing Wang; Qinli Yang (Journal of Hydrology, 2026)

Fate, bioaccumulation, and toxic responses of PFOA, PFOS, and GenX in the paddy soil–rice system across the full growth cycle - Wantong Tang; Xin Xiao; Enhui Wu; Kun Wang; Xinfei Ge; Xiaoying Zhu; Chiheng Chu; Baoliang Chen (Journal of Hazardous Materials, 2026)

Strengthening coordination for electrolyte diluent via dipole polarization enables rapid Na+ solvation/desolvation kinetics - Yan Meng; Yuanheng Wang; Qingjiang Liu; Xingyu Chen; Enhui Wang; Weihua Chen; Hongji Pan; Jinghao Zhao; Xin Li; Jia-Yan Liang (Chemical Engineering Journal, 2025)

Self-supported Ni5P4/CoP/Ni-Foam electrode for enhancing hydroxide ion adsorption in supercapacitor applications - Weiwei Wang; Hongliang Wang; Sencheng Cai; Enhui Jin; Xinyu Zhou; Guoyu Jia; Guancheng Xu; Li Zhang (Chemical Engineering Journal, 2025)

Enhancing the identification of malonylation sites using AlphaFold2 and ensemble learning - Linlin Xu; Yuting Qian; Jiayi Yang; Xiaowei Xu; Zhiqiang Li; Yanhan Wang; Enhui Lv; Xingxing Kang; Hongwei Zhang; Yaping Lu; Fei Wang; Xin Liu (Molecular Diversity, 2025)

A multi-attribute decision-making method of cascade reservoir joint scheduling schemes considering water–sediment, eco-environment, and socio-economy in the Yellow River Basin - Donglin Li; Jieyu Li; Yuanjian Wang; Enhui Jiang; Wanjie Zhao; Gang Liu; Zhifeng Yang (Journal of Hydrology, 2025)

Annual multi-objective optimization model and strategy for scheduling cascade reservoirs on the Yellow River mainstream - Gang Liu; Enhui Jiang; Donglin Li; Jieyu Li; Yuanjian Wang; Wanjie Zhao; Zhou Yang (Journal of Hydrology, 2025)

Whole-genome resequencing reveals selection signatures in China's first rainbow trout (Oncorhynchus mykiss) strain “Shuike No. 1” - Haibing Ma; Gaochao Wang; Tianqing Huang; Enhui Liu; Wei Gu; Gefeng Xu (Aquaculture, 2025)

Study on the hydrodynamic mechanics and soil mechanical characteristics under the phenomenon of river-bottom tearing scour (RBTS) - Enhui Jiang; Yanhui Liu; Li Pan; Xianfeng He; Yan Lan; Junhua Li; Yuanjian Wang (Geomorphology, 2025)

Acetylcholinesterase-assisted photoelectrochemical solution gated graphene field-effect transistor for organophosphates pesticide detection - Hairui Wang; Enhui Hou; Na Xu; Jianfeng Wu; Shuang Gao; Ping Nie; Xuelin Zhang; Tao Yu; Limin Chang; Jianwei Xie (Food Chemistry, 2025)

Impact of Pacific decadal Oscillation on the extremely cold event frequency in the Taiwan Strait - Yimin Zhang; Yuwu Jiang; Enhui Liao; Wenfang Lu; Yaozhao Zhong; Haowei Sun; Xing Liu; Zhaoyun Wang; Xiaoran Shi (Climate Dynamics, 2025)

Revealing the pivotal role of B/N-co-doping onto carbon nanospheres for promoted sulfamethoxazole degradation and its bio-toxicity evaluation - Jing Wang; Enhui Jiang; Mingyang Jia; Baosong Xing; Chen Fang; Haoqi Wang; Jiaying Yan; Chuanying Pan; Xiang Liu; Xianyong Lan (Journal of Environmental Chemical Engineering, 2025)

The Association of Urinary Zinc with Metabolic Syndrome and the Mediating Role of Liver Enzymes in the Bouyei Ethnic Group in China - Fei Xiao; Yuxin Hu; Yuan Wang; Yuxin Zhang; Enhui Zhou; Tingting Yang; Feng Hong (Cardiovascular Toxicology, 2025)

Biological properties, synthetic pathways and anti-aging mechanisms of nicotinamide mononucleotide (NMN): Research progress and challenges - Enhui Wang; Yuting Wang; Zhaofeng Zhang; Yanfei Jiang; Chunyue Zhao (Biogerontology, 2025)

A metabolome-driven deep exploration into Moringa's medicinal efficacy - Xinyang Cai; Jiaying Yang; Jiawei Zeng; Enhui Ji; Tingting Wang; Shihuan Tang; Yi Zhang; Yue Wu; Na Guo; Junying Wei (Food Research International, 2025)

Engineered design of self-cleaning and antifouling organosilicon/eugenol-based zinc acrylate resin composite coating by forming semi-interpenetrating polymer networks - Zheng Wang; Shuhong Nie; Enhui He; Guanglei Song; Xiaohui Jiang; Xia Li; Xuefeng Yan; Liangmin Yu (Chemical Engineering Journal, 2025)

Recommendation of a Surgical Approach for Papillary Thyroid Microcarcinoma Based on Preoperative Ultrasound Features Using a Multiclass Deep Neural Network - Enhui He; Yiran Wang; Xinghao Wang; Zhanxiong Yi; Marcin Grzegorzek; Peipei Yang; Xiangdong Hu; Ying Feng; Zhixiang Wang (Journal of Medical and Biological Engineering, 2025)

The analysis and optimization of S-CO2 coal fired power generation system using the split method - Yuandong Guo; Enhui Sun; Jinliang Xu; Cheng Chang; Zhaofu Wang (Process Safety and Environmental Protection, 2025)

Settlement prediction of a high embankment based on non-linear regression and neural network algorithm - Enhui Yang; Kai Wang; Jinhong He; Kaiwen Liu; Junxin Wang; Haopeng Zhang; Yanjun Qiu (Transportation Geotechnics, 2025)

Characteristics and Functions of Rhizosphere Bacterial Communities of Camelli sinensis cv. Shifocui with Cold Resistance Characteristics in Anhui Province, China - Shuiqin Shi; Enhui He; Junjie Ma; Mengrui Ge; Jiahui Gao; Tianyi Peng; Yu Fu; Jianfen Wang; Li Gong; Duoqi Zhou; Yafang Liu (Current Microbiology, 2025)

Evaluation of the acute toxic effects of ammonia on juvenile ussuri cisco (Coregonus ussuriensis) based on histopathology, antioxidant enzyme activity, immune response and the integrated biomarker response - Gefeng Xu; Yucai Pan; Wei Gu; Tianqing Huang; Enhui Liu; Gaochao Wang (Marine Pollution Bulletin, 2024)

Time-varying parameters of the hydrological simulation model under a changing environment - Ruimin Liu; Ying Luo; Qingrui Wang; Yue Wang; Yue Liu; Xinghui Xia; Enhui Jiang (Journal of Hydrology, 2024)

Influence of increasing acclimation temperature on growth, digestion, antioxidant capacity, liver transcriptome and intestinal microflora of Ussruri whitefish Coregonus ussuriensis Berg - Kaibo Ge; Ze Fan; Tianqing Huang; Wei Gu; Gaochao Wang; Enhui Liu; Runlei Pan; Datian Li; Yunchao Sun; Zuochun Yao; Liwei Wang; Cheng Zhao; et al. (Fish & Shellfish Immunology, 2024)

Effects of Exogenous Hormones on Spawning Performances, Serum Gonadotropin and Sex Steroid Hormone in Manchurian Trout (Brachymystax lenok) during Sexual Maturation - Yucai Pan; Gefeng Xu; Tianqing Huang; Wei Gu; Enhui Liu; Gaochao Wang (Fishes, 2024)
The objective of this study was to investigate the effects of salmon gonadotropin releasing hormone analog (S-GnRH-A) and human chorionic gonadotropin (HCG) on the serum levels of gonadotropins (GtHs) and sex steroid hormones in Manchurian trout during sexual maturity. Females in the treatment group were injected with 20 µg/kg S-GnRH-A and 400 IU/kg HCG, whilst males were injected with half the amount. Blood samples were collected at 0, 5, 10, and 20 days post injection (dpi). The results showed an increase in female follicle-stimulating hormone (FSH) levels in the treatment group at 5 dpi, and from 5 dpi onwards, a difference was observed between the groups, with higher FSH levels in the treatment group compared to the control group. In males, FSH levels showed group differences at only 5 dpi (p

Characteristics and influencing factors of greenhouse gas emissions from reservoirs in the Yellow River Basin: A Meta-analysis - Shurui Huang; Peijia Zhang; Wenxiu Zheng; Jiajia Zhang; Yang Li; Yuanjian Wang; Enhui Jiang; Shaoda Liu; Xinghui Xia (Science China Earth Sciences, 2024)

Effect of fly ash micromotors on expression of antibiotic resistance genes in straw composting - Jiaoyu Ren; Yanyan Cuan; Enhui Ma; Zhuxin Wang; Guangyuan Xie; Hong Wang (Journal of Environmental Chemical Engineering, 2024)

The novel probiotic preparation based on Lactobacillus spp. mixture on the intestinal bacterial community structure of Cherry Valley duck - Shuiqin Shi; Mengrui Ge; Yan Xiong; Yixun Zhang; Wenhui Li; Zhimuzi Liu; Jianfen Wang; Enhui He; Liming Wang; Duoqi Zhou (World Journal of Microbiology and Biotechnology, 2024)

Can three-dimensional nitrate structure be reconstructed from surface information with artificial intelligence? — A proof-of-concept study - Guangyu Gary Yang; Qishuo Wang; Jiacheng Feng; Lechi He; Rongzu Li; Wenfang Lu; Enhui Liao; Zhigang Lai (Science of The Total Environment, 2024)

Development of polymorphic simple sequences repeats markers from whole gene resequencing data comparison of 68 Oncorhynchus mykiss - Haibing Ma; Tianqing Huang; Enhui Liu; Gaochao Wang; Wei Gu; Gefeng Xu (Frontiers in Marine Science, 2024)
Rainbow trout ( Oncorhynchus mykiss ) is a significant cold-water fish farmed in China. Currently, most molecular marker-assisted breeding applications in rainbow trout rely on SSR markers. Although many rainbow trout SSR markers have been developed, methods for mining many polymorphic SSR markers from the genome and identifying them efficiently and rapidly are still lacking. For this reason, this study used in silico simulation method to rapidly develop a large number of polymorphic SSR markers quickly. A total of 354,613 SSR loci with two to six nucleotide repeat motifs were mined from 32 chromosomes of the rainbow trout reference genome using GMATA. The chromosome sequences of the reference genome were then aligned to the whole genome sequencing data (10×) of 68 rainbow trout samples. In silico genotyping was performed using the HipSTR programme to compare and count the variation in the number of repeats of the motifs of the SSR loci in the samples. The loci with high deletion rates and monomorphism were discarded, while those with more than one non-reference allele were kept. The final set of polymorphic SSR loci screened was 78,828. Finally, 4,821 SSR loci were selected with more than 3 alleles and no deletion in all rainbow trout samples and were physically mapped. The average polymorphic information content of these loci was 0.692, indicating high levels of polymorphism. These SSRs were utilized to analyse the genetic diversity and population structure of the 68 rainbow trout samples. The results showed that these 68 samples were divided into two groups. These newly discovered polymorphic SSR markers will provide valuable information for evaluating the construction of rainbow trout family lines for genetic diversity and improvement.

Air-sea CO2 flux in the Gulf of Mexico from observations and multiple machine-learning data products - Zelun Wu; Hongjie Wang; Enhui Liao; Chuanmin Hu; Kelsea Edwing; Xiao-Hai Yan; Wei-Jun Cai (Progress in Oceanography, 2024)

A comprehensive assessment indicator of the water-energy-food nexus system based on the material consumption relationship - Lingang Hao; Jingjie Yu; Ping Wang; Chunhui Han; Boris Gojenko; Bo Qu; Enhui Jiang; Sherzod Muminov (Journal of Hydrology, 2024)

Identification and molecular characterization of two liver expressed antimicrobial peptides (LEAPs) in Amur grayling (Thymallus arcticus grubei Dybowski, 1869) - Baorui Cao; Enhui Liu; Tianqing Huang; Wei Gu; Gaochao Wang; Bingqian Wang; Gefeng Xu (Aquaculture, 2024)

The coupling coordination and spatiotemporal evolution of industrial water-energy-CO2 in the Yellow River Basin - Ken Sun; Jingmin Han; Qianru Wu; Weisheng Xie; Wenbo He; Zhenzhen Yang; Yuanbiao Wang; Jiacheng Liu; Enhui Shi (Science of The Total Environment, 2024)

An integrated water resources management model considering carbon source and sink under uncertainty: A case study of agricultural water-dominated basin - Donglin Li; Qiting Zuo; Enhui Jiang; Zhizhuo Zhang; Qingsong Wu; Yuanjian Wang (Journal of Cleaner Production, 2024)

Genome-wide identification of simple sequence repeats and development of polymorphic SSR markers in brown trout (Salmo trutta) - Haibing Ma; Tianqing Huang; Wei Gu; Enhui Liu; Gaochao Wang; Bingqian Wang; Jianshe Zhou; Gefeng Xu (Conservation Genetics Resources, 2023)

Single and joint toxic effects of waterborne exposure to copper and cadmium on Coregonus ussuriensis Berg - Wei Gu; Kai Ji; Tianqing Huang; Enhui Liu; Gaochao Wang; Xiulan Shi; Fulin Dong; Bingqian Wang; Xubin Zhang; Xiance Wang; Gefeng Xu (Ecotoxicology, 2023)

A Comparative Study of the Effects of Extrusion on Lignocellulose Structure and Biogas Production from Wheat Straw and Digested Wheat Straw - Guangyin Chen; Hainan Cao; Changping Zhao; Wanrong Zhang; Jiawei Zheng; Enhui Wang (BioEnergy Research, 2023)

Use of a wheat straw covering to reduce nitrogen loss during pig slurry storage and reuse of the straw covering in biochar production for nitrogen retention in the slurry - Guangyin Chen; Pei Wu; Jinzhu Dong; Jiawei Zheng; Enhui Wang (Waste Management, 2023)

Degradation reduces greenhouse gas emissions while weakening ecosystem carbon sequestration of Moso bamboo forests - Ning Yuan; Enhui Wang; Shaofeng Lv; Xiaoping Tang; Tongying Wang; Gang Wang; Yufeng Zhou; Guomo Zhou; Yongjun Shi; Lin Xu (Science of The Total Environment, 2023)

Ultra-stable and bifunctional free-standing SiC photoelectrocatalyst for water remediation - Shuang Liu; Tao Yang; Enhui Wang; Hailong Wang; Zhentao Du; Sheng Cao; Qiaobao Zhang; Kuo-Chih Chou; Xinmei Hou (Journal of Cleaner Production, 2023)

Development of a spectrum-based ship fuel sulfur content real-time evaluation method - Hao Wu; Chao Wang; Enhui Chen; Zhirui Ye (Marine Pollution Bulletin, 2023)

Negatively regulation of MAVS-mediated antiviral innate immune response by E3 ligase RNF5 in black carp - Jun Yan; Guoxia Qiao; Enhui Wang; Yuqing Peng; Jiamin Yu; Hui Wu; Meiling Liu; Jiagang Tu; Yongan Zhang; Hao Feng (Fish & Shellfish Immunology, 2023)

Adsorption properties and mechanism of zinc acrylic carbon nanosphere aggregates for perfluorooctanoic acid from aqueous solution - Enhui He; Ning Liu; Yu Zhou; Zheng Wang; Xiaolan Lu; Liangmin Yu (Environmental Pollution, 2023)

Optimization of Ni Co1--Mn Se2 composition for efficient sodium storage - Yumei Liu; Zuguang Yang; Enhui Wang; Quan Kuang; Yong Ming; Benhe Zhong; Zhenguo Wu; Xiaodong Guo (Chemical Engineering Journal, 2023)

PHR1 positively regulates phosphate starvation-induced anthocyanin accumulation through direct upregulation of genes F3’H and LDOX in Arabidopsis - Zhongjuan Liu; Xueqian Wu; Enhui Wang; Yanan Liu; Yi Wang; Qinghua Zheng; Yizhen Han; Zhongze Chen; Yongqiang Zhang (Planta, 2022)

Semisolid Extrusion 3D Printing of Propranolol Hydrochloride Gummy Chewable Tablets: an Innovative Approach to Prepare Personalized Medicine for Pediatrics - Chunxiao Zhu; Yang Tian; Enhui Zhang; Xiang Gao; Hui Zhang; Nan Liu; Xiaolu Han; Yong Sun; Zengming Wang; Aiping Zheng (AAPS PharmSciTech, 2022)

Medium and Long-term Precipitation Prediction Using Wavelet Decomposition-prediction-reconstruction Model - Yongtao Wang; Jian Liu; Rong Li; Xinyu Suo; EnHui Lu (Water Resources Management, 2022)

Porcine deltacoronavirus and its prevalence in China: a review of epidemiology, evolution, and vaccine development - Pan Tang; Enhui Cui; Yihong Song; Ruoqian Yan; Jingyu Wang (Archives of Virology, 2021)

Evaluating Runoff-Sediment Relationship Variations Using Generalized Additive Models That Incorporate Reservoir Indices for Check Dams - Lingqi Li; Kai Wu; Enhui Jiang; Huijuan Yin; Yuanjian Wang; Shimin Tian; Suzhen Dang (Water Resources Management, 2021)

NaCl-induced expression of AtVHA-c5 gene in the roots plays a role in response of Arabidopsis to salt stress - Aimin Zhou; Enhui Liu; Hongping Ma; Shuang Feng; Shufang Gong; Jingang Wang (Plant Cell Reports, 2018)

Characterization and Development of EST-SSR Markers from a Cold-Stressed Transcriptome of Centipedegrass by Illumina Paired-End Sequencing - Pengliang Wang; Liping Yang; Enhui Zhang; Zihai Qin; Huayu Wang; Yongyan Liao; Xiaoyun Wang; Lei Gao (Plant Molecular Biology Reporter, 2017)

Wound healing by a 3.2 kDa recombinant polypeptide from velvet antler of Cervus nippon Temminck - Enhui Zha; Shenyang Gao; Yuzhen Pi; Xingxia Li; Yutain Wang; Xiqing Yue (Biotechnology Letters, 2012)